2021
DOI: 10.1182/bloodadvances.2020003865
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for seasonal human coronavirus lower respiratory tract infection after hematopoietic cell transplantation

Abstract: Data are limited regarding risk factors for lower respiratory tract infection (LRTI) caused by seasonal human coronaviruses (HCoVs) and the significance of virologic documentation by bronchoalveolar lavage (BAL) on outcomes in hematopoietic cell transplant (HCT) recipients. We retrospectively analyzed patients undergoing allogeneic HCT (4/2008-9/2018) with HCoV (OC43/NL63/HKU1/229E) detected by polymerase chain reaction during conditioning or post-HCT. Risk factors for all manifestations of LRTI and progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
(86 reference statements)
1
7
0
Order By: Relevance
“…Influenza vaccines in allogeneic HCT recipients may also impact outcomes, but this remains to be determined in future studies [ 7 ]. The variable definitions in this study were consistent with those in prior studies by their group and others [ 6 , 8 , 9 ], including LRTI and lymphopenia. The Use of consistent variable definitions across studies increases the reliability of quantitative models like the ISI score in predicting outcomes from respiratory viral infections, which will lead to better design and planning of future clinical trials in this patient population.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Influenza vaccines in allogeneic HCT recipients may also impact outcomes, but this remains to be determined in future studies [ 7 ]. The variable definitions in this study were consistent with those in prior studies by their group and others [ 6 , 8 , 9 ], including LRTI and lymphopenia. The Use of consistent variable definitions across studies increases the reliability of quantitative models like the ISI score in predicting outcomes from respiratory viral infections, which will lead to better design and planning of future clinical trials in this patient population.…”
supporting
confidence: 88%
“…These factors include neutropenia (absolute neutrophil count <500/μl), lymphocytopenia (absolute lymphocyte count <200/μl), patient age of at least 40 years, use of a myeloablative conditioning regimen, acute or chronic graft-versus-host disease, use of corticosteroids within 30 days of RSV infection, and transplantation within 30 days of or in the pre-engraftment period during RSV infection [ 1 ]. This quantifiable ISI stratifies patients into low-risk (0–2), moderate-risk [ 3 6 ], and high-risk (≥7) categories regarding progression or death. Studies have validated the ISI for different respiratory viral infections in allogeneic and autologous HCT recipients at multiple centers with varying success [ 2 6 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…IFP infection following a procedure, MR Mendelian randomization, DM/SIFP Diagnosesmain/secondary ICD10: T81.4 infection following a procedure, r2 the proportion of phenotypic variation explained by genetic variants, SD standard deviation Discussion Some retrospective cohort studies reported albumin as an independent risk factor for infections. Ogimi et al suggested that albumin < 3g/dL was associated with occurrence of seasonal human coronavirus lower respiratory tract infection [37]. Zhongyuan et al suggested that preoperative serum albumin < 3.5g/dL was signi cantly correlated with surgical site infection (SSI) and postoperative serum albumin < 3.0 g/dL was signi cantly correlated with surgical wound dehiscence in lumbar spine surgeries [12].…”
Section: Resultsmentioning
confidence: 99%
“…Initial thoughts suggested that hCoV infections were relevant only in the context of co‐infections 16,186 . In contrast, recent studies 11,98 have shown that around 9% to 33% of hCoV infections progress to LRTD and lead to hospitalization in 19% of cases. In this line, the presence of hCoV in BAL samples was significantly associated with high rates of respiratory support and mortality, 187 similar to other CARVs including RSV, influenza virus and hPiV 187 .…”
Section: Respiratory Virusesmentioning
confidence: 99%